Bilateral corneal perforation due to vitamin A deficiency in a child with seizures - Maiah Zarrabi; Giovanni A. Campagna; Xander Parisky; Irwin Weiss; Simon Sheung Man Fung (Global Pediatrics, 2024)
Dietary vitamin A deficiency is exceptionally rare in resource-rich countries. A well-known consequence of vitamin A deficiency is xeropthalmia, a spectrum which includes pathologic dryness of the conjunctiva and cornea, which can lead to corneal infection, thinning, or perforation, portending a very poor visual prognosis. This case describes a 10-year-old boy with Lennox-Gastaut syndrome and autism who developed malnutrition and deficiencies of multiple micronutrients, including copper, zinc, and an undetectable vitamin A blood level, secondary to dietary restriction for seizure control. After experiencing 3 months of nonspecific symptoms of ocular surface disease including eye dryness, eye redness, and tearing, he developed rapidly progressive keratomalacia and polymicrobial corneal ulcers. Despite treatment with topical antibiotics, he ultimately suffered bilateral corneal perforation requiring full-thickness corneal transplants. This report aims to raise the awareness of potentially debilitating nutrient deficiencies related to restricted diets, which are becoming increasingly common in numerous chronic pediatric conditions including epilepsy. This report also brings attention to the severe, long-term complications that can arise from nutrient deficiencies. Pediatric providers should consider a diagnosis of vitamin A deficiency in any child with a history of a restricted diet and ophthalmological symptoms.